The Impact Of Technology Acceptance Model (Tam) On The Intentity Of E-Filing Users Individual Taxpayers Tax Services Office (Kpp) Pratama Medan Timur - Chandra Desman A Situmorang; Desi Triana Munthe (Yayasan Multidimensi Kreatif, 2024)
This research aims to analyze the impact of the factors included in the Technology Acceptance Model (TAM) on the intensity of use of the e-Filing application by individual taxpayers at the East Medan Pratama Tax Service Office (KPP). Using an associative research approach, this research measures the association between Perceived Usefulness (X1), Perceived Ease (X2), and Perceived Information Technology Readiness (X3) on Intention to Use (Y) of the e-Filing application. A pre-survey of 30 taxpayers in Medan City showed a low perception of the usefulness, convenience and readiness of information technology related to e-Filing, which was reflected in the majority's low intention to use it. The research sample consisted of 380 respondents and used multiple regression analysis to predict the intensity of e-Filing use based on these three variables. The results of the analysis show that Perceived Usefulness, Perceived Ease, and Perceived Information Technology Readiness each have a positive and significant influence on Intention to Use. Overall, these three variables also have a positive and significant effect on the intention to use e-Filing. These results indicate that increasing the perception of usefulness, convenience and readiness of information technology can increase the intention to use the e-Filing application among taxpayers. This research suggests the need for increased education and training to increase perceptions of usefulness and ease of use, as well as information technology readiness among users. In addition, further research is recommended to add other variables of accounting concentration, such as level of financial literacy or experience using accounting technology, to provide more comprehensive insight into the factors that influence the adoption of e-Filing technology.